The Role of Self-Driving Vehicles in Sustainability and Road Safety from a Generation-Specific Perspective - Gabor Kiss; Mónika Garai-Fodor (Decision Making: Applications in Management and Engineering, 2024)
A key milestone in technological development, self-driving vehicles are at the heart of the study, a solution that will significantly transform the future of transport. Consumer perceptions of self-driving vehicles are examined from a generation-specific perspective. We seek to answer the question of which of the generations, which differ significantly in terms of values, consumer habits and preferences, should be considered the most potential target market for self-driving cars. In a primary research project, we investigated the perception of self-driving cars by each generation in relation to the individual and the relation between traffic safety and conditions of use. The research used a quantitative method of random sampling to analyse 8663 evaluable responses. Based on the results, we were able to identify and statistically verify generational differences in consumer opinions on self-driving cars and to characterise distinct consumer segments based on the purchase criteria for self-driving cars